(untitled) (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
POLITICAL ROLE OF ZAWISZA OF KUROZWĘKI This work is an attempt to show political career of one of Małopolska noblemen, who was elevated to the highest rank during the reign of Louis d’Anjou, King of Hungary. The twelve years of the rule of this king of d’Anjou dynasty in Poland have not been often described in historical studies, since that period did not distinguish itself in our history. For that monarch, the most important issue was to ensure succession of the throne to his daughters, and all activities of this king were aimed at the fulfillment of this goal. Cracow noblemen helped Louis to achieve this, which had significant impact on the history of Poland. Zawisza of Kurozwęki was among the most active in that field. He was from the Poraj Różyc family, son of Dobiesław, the castellan of Cracow. During the reign of Casimir the Great he achieved the dignity of Cracow archdeacon; he also participated in developing the statutes of the royal salines. The death of the last king of the Piast dynasty divided recently united Poland into two parties. The Wielkopolska noblemen and part of the clergy were agianst Louis and supported Kazimierz’s grandson Kaźko, Prince of Słupsk, as pretender to the Polish throne. Małopolska nobles supported d’Anjou dynasty. One of the results of this conflict is an account by Janko of Czarnków, Gniezno archdeacon, vice-chancellor and author of a chronicle, in which Zawisza is said to plot against him to deprive him of his office. For a long time this chronicle was the only source referring to this matter, and Zawisza was shown as an unscrupulous man, who did not hesitate to accuse the innocent to achieve the position he wanted. However, a sentence against Czarnkowski found Jan Dąbrowski by in Hungary, cast some light at that event and caused a more critical view on what the archdeacon said. As vice-chancellor, Zawisza accompanied the regent Elisabeth, daughter of King Władysław the Short, entrusted with the mission to carry into effect the succession for d’Anjou. After Janusz Suchywilk achieved the office of archbischop, Zawisza was appointed chancellor. In September 1374 a compromise between the king and the Polish noblemen was achieved in Koszyce. Zawisza is attributed the charter which was issued at that meetings in which the Budzin treaty was abolished, and the kings’ daughters were appointed successors of the throne for some concessions on behalf of Polish nobles the king accepted. In 1376 Kurozwęcki took part in a campaign against Władysław Biały, and successfully negotiated the peace with this prince. The death of Princess Catherine designated for the Polish trone, brought up the matter of succession once again. In the convention in Koszyce in 1379, opposing Wielkopolska noblemen refused to pay homage to another daughter of the king. They were forced to surrender, however, when the city gates were closed, a solution suggested by Zawisza. In 1380 Kurozwęcki became Cracow bishop. Shortly after the death of Elisabeth in March 1381, Louis, at the meeting in Buda, appointed governors to rule the country as his proxies. Zawisza Kurozwęcki was at the head of them. They succeded in establishing an agreement with the clergy in the autumn of 1381. Kurozwęcki died on 12 February, 1382. He was buried with great pomp in the Cracow Cathedral. After his death Loouis did not appoint any other person to the office of the king’s proxy.